PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANSASI DI SDN PUCUNG III KEC. KOTA BARU KABUPATEN KARAWANG - Ridwal Ridwal (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2018)
The purpose of this study was to determine the effect of Transformational Leadership, Organizational Culture and Job Satisfaction on the teacher's organizational commitment by referring to Maptuhah's opinion that there was an influence between Transformational Leadership, Organizational Culture and Job Satisfaction on Teacher's Commitment. The research method used in this study is a quantitative method through a survey with a population of 28 people with saturated samples, meaning that the entire population becomes a sample. Based on the analysis with the help of SPSS version 23 for windows shows that: Transformational leadership affects organizational commitment, this is indicated by the value of R Square of 0.066 or 6.6% while the Organizational Culture influences the Organizational commitment shown by the R Square value of 0.216 or 21.6% and Job Satisfaction have a significant positive influence on Organizational Commitment, this is indicated by the R Square value of 0.673 or 67.3%. Transformational Leadership, Organizational Culture and Job Satisfaction together have a significant positive influence as indicated by the R Square value of 0.746 or 74.6%. The empirical findings indicate that to increase Organizational Commitment teachers need to pay attention to teacher job satisfaction at SDN Pucung III, Kota Baru District, Karawang Regency. Transformational leadership and organizational culture need not be a concern.